Hydrothermal Compost Catalyst (HCC): reducing food waste and methane emissions through optimized composting - Khalit, Muhammad Ilham; Tharazi, Izdihar; Baharin, Mohd Hazrin; Adull Manan, Nor Fazli; Abdul Halim, Nurul Hayati; Mohd Salleh, Farrahshaida (Universiti Teknologi MARA Cawangan Pulau Pinang, 2025)
Food waste contributes significantly to greenhouse gas emissions, particularly methane from landfills. This study presents a Hydrothermal Compost Catalyst (HCC) designed to accelerate composting while reducing environmental impact. The system integrates mechanical shredding, thermal treatment at 60 °C, and automated mixing in a compact, cost-effective unit. The prototype was fabricated using stainless steel, incorporating induction heating and microcontrollerbased monitoring. Cabbage waste was used as the model feedstock to evaluate composting performance over a 180-minute cycle. CHNS elemental analysis revealed a sharp reduction in the carbon-to-nitrogen ratio, from 1268:1 at 60 minutes to 1.67:1 at 180 minutes. This indicates rapid organic matter breakdown and nutrient release, typically seen only after weeks in conventional composting. Visual observations also suggested reduced leachate formation. Compared to existing systems like the Hotbin and Hydrothermal Reactor, the proposed design achieved similar results with greater simplicity and lower cost. The Hydrothermal Compost Catalyst demonstrates strong potential for small-scale and urban food waste management. Its fast processing, affordability, and ease of use have made it suitable for decentralized composting. Future work will explore its effectiveness with various organic waste types and include quantitative leachate analysis to further assess environmental benefits.